The Transformation Of Balinese Arak: A Strategic Roadmap From Sacred Rituals To Global Premium Souvenirs - Dewa Ayu Diyah Sri Widari; Dewa Putu Oka Prasiasa; I Made Trisna Semara (Institut Pariwisata dan Bisnis Internasional, 2026)
This study examines the transformation of Balinese Arak from a socio-religious ritual instrument into a premium global souvenir. Despite its cultural significance, traditional artisans face industrial dualism, including legal barriers and non-standardized packaging. Using a qualitative descriptive approach, the research employs case studies and in-depth interviews with traditional producers in Karangasem and Buleleng, alongside premium industrial players. This research is critically important as it addresses the widening gap between celebratory heritage policies and the economic precariousness of indigenous producers. Findings reveal that repositioning arak as a world-class souvenir is driven by branding professionalization and diplomatic recognition at the 2022 G20 Summit. However, a structural paradox is identified where Governor Regulation Number 1 of 2020 inadvertently creates economic disparities between established downstream industries and constrained upstream artisans. By highlighting this disparity, the study provides a necessary intervention in the discourse of cultural commodification, ensuring that global premiumization does not come at the cost of local artisan marginalization. Theoretically, this study enriches literature on commodifying sacred objects while maintaining authenticity. Practically, it provides a strategic roadmap for local artisans and inclusive policy recommendations to bridge the gap between micro-producers and premium tourism markets.